2019
DOI: 10.1002/rse2.110
|View full text |Cite
|
Sign up to set email alerts
|

Assessing regional‐scale variability in deforestation and forest degradation rates in a tropical biodiversity hotspot

Abstract: Deforestation and forest degradation are major drivers of global environmental change and tropical forests are subjected to unprecedented pressures from both. For most tropical zones, deforestation rates are averaged across entire countries, often without highlighting regional differentiation. There are also very few estimates of forest degradation, either averaged or localized for the tropics. We quantified regional and country‐wide changes in deforestation and forest degradation rates for Madagascar from Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…With the CBD post-2020 framework being decided in 2021, there is still little evidence for Madagascar on the effectiveness of the protected area network for protecting its biodiversity heritage. While deforestation continues unabated (e.g., [15,18]), studies conducted by Eklund et al [19] or Yesuf et al [20] concluded that PAs in Madagascar could slow down deforestation. While Madagascar now has a network of protected areas across its main forests, only a few sites receive the bulk of attention from research, tourism, and NGOs [15,16,21].…”
Section: Introductionmentioning
confidence: 99%
“…With the CBD post-2020 framework being decided in 2021, there is still little evidence for Madagascar on the effectiveness of the protected area network for protecting its biodiversity heritage. While deforestation continues unabated (e.g., [15,18]), studies conducted by Eklund et al [19] or Yesuf et al [20] concluded that PAs in Madagascar could slow down deforestation. While Madagascar now has a network of protected areas across its main forests, only a few sites receive the bulk of attention from research, tourism, and NGOs [15,16,21].…”
Section: Introductionmentioning
confidence: 99%
“…Deforestation has had a wide impact on environmental, economic, institutional and socio-political aspects, especially those related to the accessibility and biodiversity of forest resources [7]. The rate of deforestation in Indonesia continues to occur due to various factors such as illegal logging, forest fires, weak control and supervision of the operationalization of the licensing system in forest area management, conversion of forest area functions to plantations, settlements and/or other non-forestry development purposes, all of which cannot be denied to have caused damage and destruction to forest resources [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The native vegetation of the island is treated in detail elsewhere (Gautier et al 2018, Lowry II et al 2018, with specific reference to the PA system of Madagascar. Loss of natural forests is the greatest threat to the terrestrial biodiversity of the island, and the pressure remains considerable (Vieilledent et al 2018, Yesuf et al 2019.…”
Section: Study Settingmentioning
confidence: 99%